Implementasi Kebijakan Pemberian Vaksin Bagi Calon Jamaah Haji di Dinas Kesehatan Kabupaten Karawang - Cahyono, Fadli Septian; Hermana, Cecep (Jurnal Ilmiah Wahana Pendidikan, 2023)
The government has established various vaccination policies for Hajj pilgrims based on existing legal foundations. The health examination of the Hajj pilgrims is conducted in several stages, including COVID-19 vaccination and meningitis vaccination. Health education is also provided to broaden the pilgrims' knowledge and change their behaviors. Based on research findings, it is recommended to ensure that vaccination policies align with established guidelines, enhance health education, ensure that healthcare teams have sufficient knowledge, and provide adequate quarantine facilities. The Health Department also needs to maintain coordination with relevant agencies and monitor and evaluate the implementation of the Hajj vaccination policy.